Strategi Chat & Buy, Ketepatan Barang dan Harga dalam Meningkatkan Penjualan pada PT. MAP Aktif Adiperkasa Tbk - Andika Ferdinand; Markus Manurung; Tri Kokoh Anugrah Nainggolan (IPM2KPE, 2024)
This research aims to analyze the influence of the chat & buy strategy, accuracy of goods and prices on increasing sales at Sports Station Medan Mall Floor 3. The research method used is a quantitative approach using 100 customer samples selected through the cluster sampling method. The results of the analysis show that the chat & buy strategy variables, item accuracy, and price positively and significantly influence sales increases, with a coefficient of determination (Adjusted R Square) of 0.485, which means that 48.5% of the variation in sales increases can be explained by the three variables. the. The t test shows that the chat & buy strategy, item accuracy, and price significantly influence the increase in sales, with sig values of 0.007, 0.002, and 0.000 respectively, and Tcount values of 2.766, 3.136 and 7.496 respectively. The conclusion is that the chat & buy strategy, accuracy of goods and prices play a significant role in increasing sales at Sports Station Medan Mall Floor 3. Keywords: Price, Accuracy of Goods, Increased Sales, Chat & Buy Strategy